PELATIHAN DAN PENDAMPINGAN PENGGUNAAN MEDIA DIGITAL UNTUK MENINGKATKAN DAYA SAING UMKM LOKAL DI DESA MANGKAI LAMA KECAMATAN LIMA PULUH KABUPATEN BATU BARA PADA ERA EKONOMI DIGITAL - Muhammad Fadhil Royhan Nasution; Isma Tara; Dwi Marlena; Laysya Fadiah Azza; Sukiati, Sukiati (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The digital era and the emergence of Industry 4.0 and 5.0 require Micro, Small, and Medium Enterprises (MSMEs) to utilize technology for business development and competitiveness. This study aims to enhance the digital marketing capabilities of MSME actors in Mangkai Lama Village, enabling them to use digital media for product promotion and marketing. The method applied was participatory training and mentoring involving 10 MSME participants from various business sectors. The activities included introducing digital platforms such as INAPROC, PaDi, Shopee Partner, and OLX, as well as marketing strategies through social media such as WhatsApp, Instagram, Facebook, and TikTok. The results show an improvement in participants’ understanding and skills in using digital media, managing business accounts, creating promotional content, and engaging with customers. The training effectively encouraged MSMEs to adapt to technological developments, expand market reach, and strengthen competitiveness in the digital economy.